PENGARUH PENGGUNAAN STRATEGI INTERAKTIF TERHADAP KEMAMPUAN BERBICARA SISWA - Novita Puspahaty (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2014)
This research entiltled: The Influence of Interactive Strategy Toward Students’ Speaking ability (A Study Toward Eleventh Grade at SMA Negeri 1 Cibarusah Bekasi). The objective of this research is to know the influence of Interactive Strategy Toward Students’ Speaking ability at the elventh grade of SMA Negeri 1 Cibarusah Bekasi. The writer used quasi experimental design in this research. The data of students’ speaking ability were gathered from pre-test and post-test result. In practice, then it was done by time series design. Population of the research is 220 students that are devided into 5 classes at the elevents grade of SMA Negeri 1 Cibarusah Bekasi. Further, the writer used cluster sampling and took one class consist of 40 students as an experiment class. The writer also can put forward that interactive strategy has significance influence in speaking ability. T is proved that accounted t = 9.649 are pre-test and post-test I, pre-test and post-test II = 19.32, and pre-test and post-test III = 7.90, meanwhile t table = 2.021. it means that t value > t table, so that the alternative hypotesis is accepted